Pengaruh Kompensasi Manajemen, Profitabilitas, Capital Intensity, dan Leverage Terhadap Tax Avoidance - Nichen Ria Pucantika Pucantika; Sartika Wulandari (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
This study aims to examine the analysis of the effect of management compensation, profitability, capital intensity, and leverage on tax avoidance in mining sub sector manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sampling method used purposive sampling in order to obtain 32 mining sub sector companies. The results showed that the variable of management compensation, capital intensity, and leverage had on effect on tax avoidance. While the profitability variable has a significant negative effect on tax avoidance. For the upcoming research, it is expected to apply other independent variable which have highly connection with tax avoidance as dependent variable. Furthermore, the research is expected to choose different company as well, in order to receive the accurate result and to describe the actual situation/condition.